Integrasi Karakter Melalui Kegiatan Keseharian Siswa pada Pembelajaran Matematika di Madrasah Ibtidaiyah - Rizkiyah, Maulidah; Hidayat, Nur (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2024)
foundation for students' noble moral qualities. This research aims to describe the implementation of character education through Mathematics learning in elementary schools. This research used a descriptive qualitative approach carried out at one of the Madrasah Ibtidaiyah in Sleman Regency involving teachers and students as research subjects. The data collection techniques used were interviews and observation. The data obtained was analyzed by condensing data, displaying data, and drawing conclusions. The results of this research are that character education is not only important in an academic context, but also in forming individuals who have strong moral and ethical values. Teachers have a big role in integrating these values ​​into daily learning, and recognition of the importance of character in education shows a commitment to forming a better generation in the future. There are nine characteristics that have been applied by teachers and students in learning mathematics, namely religious, disciplined, communicative, respecting achievement, creative, independent, honest, hard work and curiosity.